Neonatal and perinatal mortality : country, regional and global estimates (WHO, 2006)
This report provides neonatal and perinatal mortality estimates by country, regional groupings and globally. For countries that do not have data, models were developed to estimate mortality. Since data on deaths come from a number of different sources, the methods used to obtain the estimates are also described. Country-specific estimates of stillbirth and early neonatal deaths are published here for the first time. Estimates of stillbirth deaths that occur during delivery (intrapartum) by regional groupings, as well as estimates of sex ratio in neonatal, early neonatal and stillbirth mortality for the developing world are other recent contributions to the understanding of early mortality that are presented in this book. This publication will allow countries to review their achievements in the area of maternal and neonatal health and compare their results with those obtained by other countries. It is hoped that these estimates will stimulate interest in routine data collection and stress the need for better data to inform and monitor change.
Keywords: fetální úmrtnost; kojenecká mortalita; Infant Mortality; perinatologie a neonatologie; Fetal Mortality; sběr dat; Data Collection